Three in One: Temperature, Solvent and Catalytic Stability by Engineering the Cofactor‐Binding Element of Amine Transaminase. (13th June 2017) - Börner, Tim; Rämisch, Sebastian; Bartsch, Sebastian; Vogel, Andreas; Adlercreutz, Patrick; Grey, Carl
Abstract: Amine transaminase (ATA) catalyse enantioselectively the direct amination of ketones, but insufficient stability during catalysis limits their industrial applicability. Recently, we revealed that ATAs suffer from substrate‐induced inactivation mechanism involving dissociation of the enzyme–cofactor intermediate. Here, we report on engineering the cofactor‐ring‐binding element, which also shapes the active‐site entrance. Only two point mutations in this motif improved temperature and catalytic stability in both biphasic media and organic solvent. Thermodynamic analysis revealed a higher melting point for the enzyme–cofactor intermediate. The high cofactor affinity eliminates the need for pyridoxal 5′‐phosphate supply, thus making large‐scale reactions more cost effective. This is the first report on stabilising a tetrameric ATA by mutating a single structural element. As this structural "hotspot" is a common feature of other transaminases it could serve as a general engineering target. Abstract : Ready for industrial action : The insufficient stability of amine transaminases can be overcome by mutating the cofactor‐binding element. Through semi‐rational design, we introduced two point mutations that increased the melting point of the enzyme's resting and intermediate states, thus enabling amination reactions at industrially relevant temperatures, as well as high substrate and solvent content.